Topical corticosteroids: Abuse and Misuse - Yugandar Inakanti; Venkata Narsimha Rao Thimmasarthi; Anupama; Shiva Kumar; Akshaya Nagaraj; Srilakshmi Peddireddy; Abhiram Rayapati (Our Dermatology Online, 2015)
Background: The Topical Corticosteroids are among the most commonly prescribed medication in an out-patient dermatology setting since they were first introduced in early 1950s. Probably no other group of drugs has had such a profound impact on the specialty as Topical Corticosteroid. They provide rapid symptomatic relief in almost all inflammatory dermatoses, especially in the short term. Multiple pathways including rebound vasodilatation and proinflammatory cytokine release have been proposed as the mechanism for such reactions. Aim: To study various adverse effects of topical corticosteroids misuse over face. Materials and Methods: 130 patients with a history of topical corticosteroid use on face for minimum 1 month duration were included in this study. Results: Majority of patients were between age group of 21 to 30 (65.4%). Female sex preponderance over male sex with 67.8%. Majority of patients were House wives (49%) followed by Employees (23%). Duration of application of TC was 3-6 months (77%) in majority of cases. Most commonly abused TC was Betamethasone Valerate (79.2%). Conclusion: Topical Corticosteroid should not be used on the face unless it is under strict dermatological supervision.